OPTIMIZATION OF PRODUCTION STRUCTURES IN ORDER TO INCREASE COMPETITIVENESS OF AGRICULTURAL HOLDINGS - Turek Rahoveanu, Adrian; Turek Rahoveanu, Magdalena; Dinu, Toma (Economics of Agriculture, 2011)
The approach of optimizing the production structure should answer questions like: What to grow? How much of each crop? What expenses and the proft will be achieved? Taking into account these questions and that there are more possibilities of combining crops, substantiation the decisions on the new crop structure involves the use of different methods, such as: method of variants or method of linear programming. Is chosen in the end the variant considered to be the best. The option will be according to proft, the way resources are used, the extent in which is responded to different requirements that manifests to the new production structure. In this paper we decided to apply linear programming, as a method of optimizing the production structure.